Numerical Analysis on the Influence of Thickness of Liquefiable Soil on Seismic Response of Underground Structure - 夏志凡 叶冠林 王建华 叶斌 张锋 (Shanghai jiao tong da xue xue bao, 2010)
Seismic response of underground structure in liquefiable soils was analyzed by means of fully coupled dynamic finite element method. The soils were simulated by a cyclic mobility constitutive model, which is developed at the base of modified Cam-Clay model with some concepts such as stress induced anisotropy, overconsolidation and structure. It is verified that the constitutive model can perfectly described the dynamic character of both liquefiable sand and non-liquefiable clay. Special emphasis was given for the influence of thickness of liquefiable soil on the seismic response. Results showed that soils at both sides of the structure flowed toward the bottom of the underground structure with the occurrence of liquefaction, which led to the uplift of structure. The uplift of underground structure increased with the increasing of thickness of liquefiable soils.